Resveratrol Attenuates Exercise-Induced Adaptive Responses in Rats Selectively Bred for Low Running Performance - Nikolett Hart; Linda Sarga; Zsolt Csende; Lauren G. Koch; Steven L. Britton; Kelvin J.A. Davies; Zsolt Radak (SAGE Publishing, 2014)
Low capacity runner (LCR) rats have been developed by divergent artificial selection for treadmill endurance capacity to explore an aerobic biology-disease connection. The beneficial effects of resveratrol supplementation have been demonstrated in endurance running. In this study it was examined whether 12 weeks of treadmill exercise training and/or resveratrol can retrieve the low running performance of the LCR and impact mitochondrial biogenesis and quality control. Resveratrol regressed running performance in trained LCR (p<0.05). Surprisingly, exercise and resveratrol treatments significantly decreased pAMPK/AMPK, SIRT1, SIRT4, forkhead transcription factor 1 (FOXO1) and mitochondrial transcription factor A (TFAM) levels in these animals (p<0.05). Mitochondrial fusion protein, HSP78 and polynucleotide phosphorylase were significantly induced in LCR-trained, LCR-resveratrol treated, LCR-trained and resveratol treated groups compared to LCR-controls. The data indicate that the AMPK-SIRT1-NAMPT-FOXO1 axis could be important to the limited aerobic endurance capacity of low running capacity rats. Resveratrol supplementation was not beneficial in terms of aerobic endurance performance, mitochondrial biogenesis, or quality control.